Scorpion Extracts Inhibit Tumor Growth in Esophageal Cancer and Lung Adenocarcinoma - Dong, Yixuan; Wang, Jihui; Li, Jing; Li, Wei (Current Signal Transduction Therapy, 2016)
The inhibition of scorpion extracts on esophageal cancer and lung adenocarcinoma cells has been reported by previous studies, but the specific anti-tumor efficacy and potential molecular mechanism have not been clarified. In this study, we first modified the optimal enzymolysis and inactivation technology by imitating gastric and intestinal enzyme, and then investigated the antitumor effect of scorpion extracts both in vitro and in vivo. Our results showed that scorpion alcohol extraction with or without enzymolysis and fermentation could inhibit the cell proliferation of esophageal cancer and lung adenocarcinoma, and tumor growth in S180 tumor burden mice. In addition, the SOD activity increased by scorpion extracts, but MDA content decreased. The scorpion alcohol extracts without fermentation and enzymolysis exert inhibitory effect on the growth of esophageal cancer cells, and unenzymolytic fermented extracts have strong inhibitory effect on the growth of lung cancer cells. The scorpion and its extracts may serve as a new therapeutic agent to suppress tumor growth probably by promoting the function of immune organs and enhancing the activity of the immune system.
Keywords: lung cancer